Identification of a novel transthyretin mutation D39Y in a cardiac amyloidosis patient and its biochemical characterizations - Ma, Qunchao; Wang, Mengdie; Huang, Yanan; Nie, Ying; Zhang, Xin; Yang, Dan Dan; Wang, Zhuo; Ding, Siyin; Qian, Ningjing; Liu, Yu; Pan, Xiaohong (Frontiers in Cardiovascular Medicine, 2023)
Hereditary transthyretin cardiac amyloidosis (hATTR-CA) is a rare autosomal dominantly inherited disease caused by mutations in the transthyretin (TTR) gene. TTR mutations often cause the instability of transthyretin, production of misfolded proteins, and ultimately excessive deposition of insoluble amyloid fibrils in the myocardium, thereby leading to cardiac dysfunction. Herein, we report a novel transthyretin D39Y mutation in a Chinese family. We characterized the kinetic and thermodynamic stabilities of D39Y mutant TTR, revealing that TTR D39Y mutant was less stable than WT TTR and more stable than amyloidogenic mutation TTR L55P. Meanwhile, the only FDA approved drug Tafamidis showed satisfactory inhibitory effect toward ATTR amyloid formation and strong binding affinity in test tube revealed by isothermal titration calorimetry. Finally, we measured the well-folded tetrameric TTR concentration in patient’s and his descents’ blood serum using a previously reported UPLC-based assay. Notably, the tetramer concentrations gradually increased from symptomatic D39Y gene carrier father, to asymptomatic D39Y gene carrier daughter, and further to wild type daughter, suggesting the decrease in functional tetrameric TTR concentration may serve as an indicator for disease age of onset in D39Y gene carriers. The study described a Chinese family with hATTR-CA due to the TTR variant D39Y with its destabilizing effect in both kinetic and thermodynamic stabilities.